Prediction and measurement of the aerodynamic performance of a wind turbine - Benim Ali Cemal; Diederich Michael; Gül Fethi (MATEC Web of Conferences, 2018)
Aerodynamic behavior of a small wind turbine is analyzed, both experimentally and numerically. Mainly, an unsteady three-dimensional formulation is adopted, where the flow turbulence is modelled by an Improved Delayed Detached Eddy Simulation framework, using the four-equation transitional Shear Stress Transport model, as the turbulence model. A quite good agreement between the measurements and calculations is observed.